Analisis Flypaper Effect dan Kemampuan Fiskal Pemerintah Kabupaten/Kota di Indonesia - Pramudya, Farhan; Anis, Ali (Universitas Negeri Padang, 2024)
This study aims to determine the effect of: (1) Local revenue per capita on regional expenditure kabuaten/kota in Indonesia. (2) Unconditional grant per capita on district/city spending in Indonesia. (3) Previous year regional expenditure per capita on regional expenditure. (4) PAD per capita, unconditional grant per capita, and previous year's regional expenditure per capita jointly affect district/city spending in Indonesia. (5) To see the flypaper effect phenomenon in districts/cities with a very high fiscal capacity index, high fiscal capacity index, medium, low fiscal capacity index. This type of research is quantitative research with secondary data in the form of panel data, namely a combination of 2017-2021 time series data and cross section data of 508 districts / cities in Indonesia. The analysis technique used is panel data regression analysis. The results showed that: (1) local revenue per capita has a positive and significant effect on district / city regional spending in Indonesia. (2) Unconditional grant per capita has a positive and significant effect on district / city spending in Indonesia. (3) Previous year regional expenditure per capita has a positive and significant effect on district / city regional expenditure in Indonesia. (4) Simultaneously, local own-source revenue per capita, unconditional grant per capita and previous year local expenditure per capita have a positive and significant effect on district/city local expenditure in Indonesia. (5) The flypaper effect phenomenon is found in districts/cities with high, medium, low and very low fiscal capacity indices.